Identification of the Potential Biological Preservative Tetramycin A-Producing Strain and Enhancing Its Production - He, Yinglong; Ding, Yu; Wu, Qingping; Chen, Moutong; Zhao, San’e; Zhang, Jumei; Wei, Xianhu; Zhang, Youxiong; Bai, Jianling; Mo, Shuping (Frontiers in Microbiology, 2020)
The aim of this study was to develop a potential microbial preservative to prevent the growth of fungi in food. The isolate ZC-G-5 showed strong antifungal activity against food spoilage fungi and Streptomyces albulus was identified on the basis of morphologic, culture, and 16S rDNA sequence analyses. The active metabolite was elucidated as tetramycin A (TMA) through spectroscopic techniques, including HR-ESI-MS, 1D-NMR, and 2D-NMR. An antifungal activity assay revealed that the minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) of TMA were 1.50–2.50 and 3.00–5.00 μg/ml, respectively. In situ antifungal activity analyses demonstrated that 90.0 μg/ml of TMA could inhibit the growth of fungi for over 14 days. In order to enhance TMA production, the high-yield mutant strain YB101 was screened, based on the isolate ZC-G-5, using a high-throughput screening method. The best metabolic precursor was selected during fermentation, when the concentration of glycerol was 8% (v/v) in Gauze’s broth medium to cultivate the mutant strain YB101; the concentration of TMA could be increased to 960.0 μg/ml, compared with the original isolate ZC-G-5, where the concentration of the TMA was only 225.0 μg/ml. Our study may contribute to the application of S. albulus and its active metabolite as a potential bio-preservative in the food industry.